High variation in repetitive DNA fragment length for white spot syndrome virus (WSSV) isolates in Thailand - Chainarong Wongteerasupaya (2018)
White spot syndrome virus (WSSV) presently causes the most serious losses to shrimp farmers worldwide. Earlier reports of high DNA sequence homology among isolates from widely separated geographical regions suggested that a single virus was the cause. However, we have found surprisingly high variation in the number of 54 bp DNA repeats in ORF94 (GenBank AF369029) from 55 shrimp ponds (65 shrimp samples) experiencing WSSV outbreaks in Thailand in 2000 and 2002. These were detected by PCR amplification using primers ORF94-F and ORF94-R flanking the repeat region. Altogether, 12 different repeat groups were found (from 6 to 20 repeats) with 8 repeats being most frequent (about 32%). Extracts prepared from individual shrimp in the same outbreak pond belonged to the same repeat group while those collected at the same time from separate WSSV outbreak ponds, or from the same ponds at different times, usually belonged to different repeat groups. This suggested that different outbreaks were caused by different WSSV isolates. In contrast to the highly variable numbers of repeats, sequence variation within the repeat region was confined to either T or G at Position 36. These variations may be useful for epidemiological studies on the local and global movement of WSSV, since there is high variation in the number of repeats (good for local studies) but little sequence change (good for global studies).